PERAN PENGAWAS TK DALAM MEMBINA GURU TK TERHADAP PENINGKATAN KOMPETENSI GURU DI GUGUS EUPHORBIA KECAMATAN RATU SAMBAN KOTA BENGKULU - Evy Sumiati (Al Fitrah: Journal Of Early Childhood Islamic Education, 2023)
THE ROLE OF KINDERGARTEN SUPERVISORS IN TEACHER DEVELOPMENT FOR INCREASING TEACHERS' INTEREST IN THE EUPHORBIA Cluster, RATU SAMBAN DISTRICT. This study aims to describe (1) describe the teacher's interest and performance map, (2) describe the use of the program to increase the use of supervisors on teacher interest, (3) describe the implementation of construction on teachers and (4) describe the evaluation for the implementation of teacher development. This research is a qualitative research with an ethnographic approach. In determining research subjects, researchers used purposive sampling, namely determining to choose a small portion with certain considerations that are expected to provide optimal data. Methods of data collection using observation, ethnographic interviews, notes, and recorded interviews. The research was conducted in the Euphorbia Cluster, Ratu Samban District. To test the validity of the data, the researcher used the following techniques: participant length, reliable observation, data triangulation, and member checks, while the data analysis technique used was an in-citus data analysis model. In reviewing the theory, researchers used an analytic induction approach. The data obtained was submitted and analyzed to be developed based on what was provided by the informants using qualitative analysis which consisted of three activities, namely data reduction, data verification, and drawing conclusions. The conclusion from this study is the supervisor's role in teacher improvementÂ Interests are carried out by providing guidance carried out in the activities of the Euphorbia Cluster of Ratu Samban District. Teachers who actively participate in coaching conducted in the Euphorbia cluster, Ratu Samban District, have the ability to carry out school activity assignments even though there are still deficiencies.